The Freshwater Copepod Limnocalanus macrurus in the Canadian Arctic Archipelago: Numbers, Weights, and Respiration Observed from September 1961 – July 1962 - Apollonio, Spencer; Saros, Jasmine E. (ARCTIC, 2013)
Numbers, weights, and oxygen consumption of the copepod Limnocalanus macrurus were measured through the winter 1961 – 62 under the ice of Immerk Lake on Devon Island, Arctic Canada. Maximum abundance was 2361 animals per m3 found under ice in mid June, average adult wet weight was 65 μg, and hourly oxygen consumption per adult ranged from 0.26 μg in late summer to 0.03 μg in early winter. The results are compared with results from Char Lake and Resolute Lake on Cornwallis Island, Arctic Canada. The Immerk population was more stable than those at the other lakes, and weights and oxygen consumption appear to be comparable. The seasonal breeding cycle at Immerk Lake was different from that at Char Lake and similar to that at Resolute Lake. A comparison of Immerk Lake data from 1961 – 62 and 1972 – 73 showed almost identical levels of total oxygen metabolism. Immerk Lake copepod oxygen consumption was 6.5% of the total lake metabolism, while that at Char Lake was 6%. These data may assist in future assessment of climate or anthropogenic changes. Le nombre, le poids et la consommation d’oxygène du copépode Limnocalanus macrurus ont été prélevés au cours de l’hiver 1961-1962 sous la glace du lac Immerk, sur l’île Devond, dans l’Arctique canadien. L’abondance maximale se dénombrait à 2 361 animaux par m3 sous la glace au milieu de juin, tandis que le poids humide moyen d’un copépode adulte s’élevait à 65 μg, et que la consommation horaire d’oxygène par adulte variait entre 0,26 μg en fin d’été et 0,03 μg en début d’hiver. Les résultats ont été comparés aux résultats obtenus au lac Char et au lac Resolute sur l’île Cornwallis, dans l’Arctique canadien. La population du lac Immerk était plus stable que celle des autres lacs, tandis que le poids et la consommation d’oxygène de cette population semblaient comparables. Au lac Immerk, le cycle de reproduction saisonnier différait de celui du lac Char, mais il s’apparentait à celui du lac Resolute. La comparaison des données recueillies au lac Immerk en 1961-1962 ainsi ...